PENGARUH KUALITAS PRODUK DAN NILAI PELANGGAN TERHADAP LOYALITAS PELANGGAN DENGAN DIMEDIASI KEPUASAN PELANGGAN (Studi pada Pelanggan Starbucks Paragon Mall Semarang) - Septian Adhi Nugroho, 12.05.51.0052; Sutejo, Bambang (Students Journal of Economic and Management, 2016)
This study aimed to analyze the influence of Product Quality and Customer Value on satisfaction and customer loyalty Starbucks Paragon Mall Semarang. The population in this study is a Starbucks customer Paragon Semarang. The minimum sample size in this study, the number of indicators of the study were 19 so that the number of samples is 5 times the number of indicators or as many as 5 x 18 = 90. However, in this study the samples are rounded to 100. The sampling technique used purposive sampling. The criteria for the samples in this study are customers who have made purchases of more than 3 times. The analysis tool used is the test of validity, reliability, multiple linear regression and test of mediation. The results of the analysis can be concluded that: product quality positively affects customer satisfaction. Customer value positive effect on customer satisfaction. Product quality positively affects customer loyalty. Customer value positive effect on customer loyalty. Customer satisfaction has positive effect on customer loyalty. Customer satisfaction is not as mediating variables influence product quality to customer loyalty. Customer satisfaction is not as mediating variables influence customer value on customer loyalty Keywords: product quality, customer value, customer satisfaction and customer loyalty